2009
DOI: 10.1021/ja9040362
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nitric Oxide from Nitrite by the Ferriheme b Protein Nitrophorin 7

Abstract: Recently, the conversion of nitrite into NO by certain heme proteins, in particular hemoglobin, gained much interest as a physiologically important source of NO in human tissue. However, in an aqueous environment, nitrite reduction at an iron porphyrin occurs either through oxidation of ferroheme to ferriheme or with the assistance of a second substrate molecule. Here we report on the reduction of nitrite in the absence of a second substrate at the heme center of the ferriheme protein nitrophorin 7 (NP7) resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…Afterward, the reaction continues until all the heme centers are NO coordinated (see Fig. 2C, III) (43). This experiment shows that NPs act as catalysts for the nitrite disproportionation reaction at neutral pH.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Afterward, the reaction continues until all the heme centers are NO coordinated (see Fig. 2C, III) (43). This experiment shows that NPs act as catalysts for the nitrite disproportionation reaction at neutral pH.…”
mentioning
confidence: 64%
“…At this time point, similar to the reaction displayed in (B), the rate of the Soret band development increases until NP7 is saturated with NO . [For further experimental details see (43).] 2.…”
Section: Interactions Of Nps With High-molecular Weight Blood Componentsmentioning
confidence: 99%
“…The mechanisms shown here are based on those that are heme-based, molybdopterin-based, and those that function as nitrite anhydrases including nitrophorin [131, 132]. …”
Section: Highlightsmentioning
confidence: 99%
“…The viability of this reaction has recently been supported by studies of glass embedded MetHb [26]. Interestingly, it has recently been observed that nitrophorin 7, a salivary ferric hemoprotein from a blood-feeding insect, can catalzye the convertion of nitrite to NO, suggesting similar interesting biological signaling properties of a ferric hemoprotein and nitrite [27]. …”
Section: Introductionmentioning
confidence: 99%